DIALEKTIKA POLIGAMI DALAM NARASI NORMATIF DAN POTRET EMPIRIS - Fahrudin, Fahrudin (IAIN Tulungagung, 2021)
The problem of polygamy, which some internal Muslims say is teaching inherent in Islamic teachings, becomes a complicated problem when it is confronted with socio-cultural conditions, where the Muslim community resides, in various dimensions of time and space. What was previously said to have been standardized as teaching, in fact still leaves a long and dialectical debate. Even by reading a variety of classical literature, it turns out that polygamy still leaves a wide room for dialogue, and cannot be said to be a teaching that has a single value in its legality. So it becomes important when reading polygamy according to classical Islamic sources, and also how Muslim countries pay attention to polygamy problems that occur in the context of citizens who are in fact in their administrative responsibility. The symptomatic problem is the strengthening of the internal perception of some Muslims regarding polygamy. They consider that polygamy is a teaching that is recommended to be implemented. However, they often do not arrive at the spiritual value of the teachings of polygamy. How then the constitutions in various Muslim countries regulate the practice of polygamy in their countries, also becomes an interesting legal dialectic. Because indeed some of these countries loosely liberate it, while on the other hand, some strictly prohibit, or at least provide strict legal regulations in the case of polygamy. By reading polygamy through classical and contemporary Islamic sources, it is hoped that it can reopen the horizons of thinking about this problem. Also of course by looking at how the practice of polygamy law is carried out in various Muslim countries, by looking at the legal constitutions that are implemented in these countries. Because in truth the issue of polygamy is ijtihadiyah fiqhiyyah which at any time can lead to various legal conclusions, according to the context of space and time in which the law applies and is implemented. So the conclusion of the legal variant is something that must happen and needs to be shared by the Muslim community across generations.